Pumpkin seed proteins and the multifunctional properties of their hydrolysates: a review (Research, Society and Development, 2022)
Pumpkin seeds are most often discarded or intended for animal feed, despite being a promising source of protein. Several studies have demonstrated the technical-functional potential of different vegetable proteins used in food processing as ingredients to improve foaming, emulsification, and gelling properties. However, the low water solubility of pumpkin seed proteins makes their industrial application in several products difficult. To overcome this limitation, the hydrolysis of these proteins appears as a promising strategy to obtain compounds with better technical-functional properties compared to native proteins. In addition, the peptides obtained may exert potential biological properties, such as: antidiabetic, antioxidant, antihypertensive, anti-inflammatory, and antimicrobial activities. With this literature review, studies on pumpkin seed proteins, their composition and technical-functional properties were compiled. The properties of hydrolysates and bioactive peptides obtained through the enzymatic hydrolysis of pumpkin seed proteins were emphasized, to spread knowledge about the sustainable use of a protein source with high industrial potential. The works showed that enzymatic hydrolysis makes it possible to obtain bioactive peptides with relevant biological properties. However, studies should also be conducted to understand the behavior of bioactive peptides in different food matrices and in vivo systems, to recognize their bioactivities presented in vitro.